DIAGNOSIS OF THE HYPERURICEMIC SYNDROME AS THE MANIFESTATION OF MULTIMORBID PATHOLOGY IN CLINICAL EXPERIENCE OF GENERAL PRACTITIONER - Ждан, В.М.; Капустянська, А.А.; Бобирьов, В.М.; Шилкіна, Л.М.; Шепітько, В.І. (World of Medicine and Biology, 2015)
GPs need to timely detect the first signs of hyperuricemia before the development gouty arthritis and metabolic disorders.Proved that, the timely correction of hyperuricemia can be prevent the development of future cardiovascular diseases, and renal lesions. That is why the use of diagnostic algorithm hyperuricemic syndrome is crucial in the daily practice of general practitioners in order to provide the prevention of irreversible complications, disability save patients and improve their quality of life.